NUTRACEUTICALS: THE CURRENT SCENARIO - Maurya, Priyanka; Singh, Shubham; Kumari, Pooja; Mishra, Jai Narayan; Kushwaha, Ashutosh (IJRDO-Journal of Applied Science, 2022)
Nutraceuticals have gotten impressive interest due to their assumed wellbeing. The Present article centers around the requirement for devouring proper weight control plans, medical problems encompassing inability to stick to the realized smart dieting models, improvement of new nutraceuticals/useful food varieties/food supplements with novel medical advantages, clarification components of activity of these items, to characterize and comprehend the logical, detailing and administrative parts of nutraceutical. This article might go about as an apparatus to side by side with the new improvements in nutraceutical research.